LIST OF FISH SPECIES OF THE QUEGUAY RIVER BASIN, URUGUAY RIVER LOW - Paullier, Sofía; Bessonart, José; Brum, Elías; Loureiro, Marcelo (Boletín de la Sociedad Zoológica del Uruguay, 2019)
The Queguay river is one of the main tributaries of the lower Uruguay river basin. At the confluencce of its main effluents large wetlands and riparian forest are developed, that according to their biodiversity and ecosystem functions have been included in the National Protected Areas System, under the name “Montes del Queguay”. At a national scale the basin is included in two ecoregions: the Basáltic Slope and the Western Sedimentary Basin. Except for an unsupported listing in scientific collections, there is no documented information about its ichthyofauna. Therefore, the objective of this work was to prepare an updated list of the fish species in the Queguay River basin. Considering all the sources of information, a total of 94 species were registered for the basin, corresponding to 60 genera, 28 families and nine orders. The composition of species found was similar to the largest tributary of the low Uruguay ecoregion, the Río Negro basin. The main migratory species of the Plata basin stand out, as well as a species of annual fish endemic to the wetlands of the basin, and the presence of an invasive exotic species (Cyprinus carpio).